Chronology and Geomorphological Activity of the Akdag Rock Avalanche (SW Turkey) - Bayrakdar, Cihan; Gorum, Tolga; Çılğın, Zeynel; Vockenhuber, Christof; Ivy-Ochs, Susan; Akçar, Naki (Frontiers in Earth Science, 2020)
Large rock-slope failures are among the primary geohazards in high mountain areas. These rock avalanches and rockslides constitute most of the world’s largest landslide deposits. This study focuses on the formation and geomorphological activity of the Akdag landslide complex located on the southern slope of Mount Akdag, SW Turkey. We employed detailed mapping in the field, spatial and morphometric analysis using GIS and remote sensing technologies, and surface exposure dating with cosmogenic 36Cl to reconstruct the chronology of the landslide complex. For the analysis of cosmogenic 36Cl, we collected 18 surface samples from calcareous boulders within the landslide deposit. Our field mapping shows that the Akdag rock avalanche is a large and active slope failure developed between carbonates and flysch. The rock-avalanche deposits cover an area of 9.8 km2 and together with the primary and secondary slope failures which form the landslide complex, cover an area of 15 km2. The Akdag rock avalanche is one of the largest (3×108 m3) known bedrock landslides in Turkey. Cosmogenic 36Cl exposure ages indicate that the main collapse occurred at 8.3 ± 1.4 ka (2), followed by secondary failures. We dated one of the latter to 1.1 ± 0.2 ka (2). Based on field evidence, we surmise that increased water discharge in the springs along the carbonate-flysch contact zone played a key role in the Early Holocene failure.